Preparation and characterization of sequilhos-type biscuits added with almond flour of Acrocomia intumescens - Silva, Maria Michele Alves da; Feitosa, Maria Karine de Sá Barreto; Palitot, Lúcia Emanuele Barros Teixeira; Coutinho, Henrique Douglas Melo; Vasconcelos, John Eversong Lucena de; Santos, Francisco Antonio Vieira dos; Lisbôa, Cícera Gomes Cavalcante de; Raposo, António; Alfheeaid, Hani A.; Alsharari, Zayed D.; Alturki, Hmidan A.; Alhaji, Jwaher Haji; et al. (Frontiers in Nutrition, 2022)
Acrocomia intumescens ("macaúba") is a species that during processing generates a large amount of waste. The use of this residue for the production of flour for incorporation into food products is a way to minimize the cost and nutritionally enrich the final product. This work aimed to develop and analyze, in terms of physico-chemical and microbiological properties, cookies with macaúba almond cake residual flour. Sequilhos formulations were obtained using three different proportions of flour (2, 4 and 6%). The analysis of the flour allowed to find 4.29% of moisture, 1.13% of acidity, 5.33 of pH, 45.27% of carbohydrates, 28.74% of lipids, 20.06% of proteins and 2.45% of ash. In the analysis of the sequilhos formulations, the following values were found: moisture (5.03 to 8.13%), acidity (0.10 to 0.14%), pH (5.52 to 5.93), carbohydrates (61 .44 to 73.37%), lipids (18.77 to 31.77%), proteins (0.85 to 1.92%), ash (0.83 to 0.94%) and total energy value (109.11 to 133.51 Kcal/100g). In microbiological analyzes it was highlighted that the sequilhos presented adequate sanitary conditions. The results indicate almond flour as an ingredient to be incorporated in the preparation of sequilhos, which in turn, presented satisfactory physico-chemical properties and microbiological results.